A Question to Eratosthenes - Galina S. Samigullina (ARPHA Proceedings, 2022)
The inclusion of Russia in the world educational area and the signing of the Bologna Agreement, educational priorities of UNESCO, international cross-sections of students' knowledge (PISA, TIMSS), federal state standards at all levels of Russian education actualize the problem of the effectiveness of knowledge. Research, carried out by Russian scientists, was based on the acceptance of competence and cognitive approaches, as the implementation of knowledge, abilities and skills in the work of each student. At the same time, the formation of a complete image of the material world is not possible without the synthesis of two forms of expression: real (the study of real objects) and knowledge (concepts, theories, etc.). Knowledge translation which is not only within one discipline would eliminate the problem of shaping discrete vision of the world. The competency-based approach involves comprehensive domain knowledge by way of an increase of cross-curriculum components. The ability to “interpret” subject or cross-curricular skills has been developed to prepare undergraduate and practicing teachers. Research results can be used in the process of studying natural sciences and humanities. The current study helps to reduce the gap between academic sciences and general education disciplines, form holistic views on methods and ways of knowing the world, and organize an effective and high-quality educational process.